Rapid detection of methicillin-resistant Staphylococcus aureus and SCCmec types from nasal swabs by multiplex PCR - Cavalcante, Fernanda Sampaio; Abad, Eliane de Dios; Guimarães, Ana Carolina Fonseca; Saintive Barbosa, Simone; Ribeiro, Marcia; Ferreira, Dennis de Carvalho; dos Santos, Kátia Regina Netto (The Journal of Infection in Developing Countries, 2016)
This item has no abstract. Follow the links below to access the full text.